Nurses involvement in lowering fear and anxiety of pre-school children in healthcare institution - Juozapavičienė, Rasa; Čižauskaitė, Justina (Slauga. Mokslas ir praktika, 2020)
The aim of work – To reveal the fears and anxiety of preschool children in the medical institution and the actions of nurses to reduce them.Scientists say that children most fears occur from 3 years to 8 months to 5 years old. Preschool children of this age feel fear of being punished, lonely, animals, dark and imaginary creatures [3, 6]. Research has shown that 70% of preschool children feel fear and anxiety before taking medical procedures, experiencing psychological experiences in a medical facility [1, 2].Without giving enough time, attention and willingness to overcome these problems for preschool age children, they may experience anxiety disorders, psychosomatic illnesses, difficulties in communicating with each other, or even depression [3, 4]. At the medical institution the closest to a preschool child are parents and medical staff, which must also devote efforts and working time to overcoming the fear and anxiety.The research was done in 2018 September – December, it was attended by 102 nurses, which working in Kaunas city personal health care institutions. The results of the study showed that by reducing child's fear and anxiety, nurses always communicate in a language that the child understands, chooses a clear, calm voice tone, sings children's songs, plays with the child, introduces the medical instruments which use in the procedure, wears colorful medical clothes. When performed medical procedures for a child, nurses allow parents to take part together.
Keywords: nurse; preschool age children; fear; anxiety